Study Phenomenological Of Covid-19 Herbal Treatment In The Tehit Tribe, Teminabuan District, Sorong Selatan District, West Papua With A Transcultural Nursing Approach - Fitriani, Fitriani; Ribka N, Ivana; Hardiyanti, Rina (Fakultas Kedokteran, 2022)
Coronavirus 2019 (Covid-19) is a disease that has become a worldwide pandemic. Most of the Tehit people in rural areas do not continue their treatment to the hospital but prefer traditional medicine by consuming red fruit (Pandanus conoideus lam), besides red fruit there are still other medicines they use such as buahtaer (Anisoptera thurifera), buahkelapahutan (Borassus heneanus), sarangSemut (Myrmecodiasp). The Tehit tribal community believes that consuming herbal plants increases immunity so that the covid-19 virus does not attack easily and when exposed to Covid-19 symptoms are felt to be mild, recover quickly, and become a culture of the Tehit tribal community to maintain immunity with Papuan herbal medicinal plants can be an option. to fortify themselves, especially for the indigenous Papuan people who have a communal lifestyle and are a vulnerable group to being infected during this covid-19 pandemic. The purpose of this study is how the effect of alternative measures on the Covid-19 herbal treatment of the Tehit tribe. This research is a qualitative research with a phenomenological study approach. In this study, the measuring instrument used was a primary (direct) data collection technique, namely in-depth interviews. ) To test the credibility of the data, it is done by triangulation of data sources where the researcher checks the data obtained through several sources. The results of the study showed that the technology for the herbal treatment of Covid-19 of the Tehit Tribe was influenced along with the development of science and technology so that the community's demand for quality health services was also increasing. Therefore, health workers, both doctors and nurses, must improve their abilities so that the care provided can satisfy patients, besides that hospital facilities and infrastructure must be complete and supportive. So that people believe that medical healing is better than herbal treatment. Technology for the herbal treatment of COVID-19, the Tehit Tribe, needs a culture care agreement/negotiation.